Fintech: Road Ahead (International Journal of Food and Nutritional Sciences, 2022)
Fintech is the newest buzzword in the financial industry. The most recent development in Fintech, driven by startups, presents comparable issues for investors and authorities, especially in harmonizing the probable advantages of modernization with the potential hazards of innovative techniques in the financial services industry. Traditional financial institutions have transformed due to financial technology. "fintech" refers to the burgeoning technology advancements in the financial industry. The banking sector is progressively being shaped by fintech. The financial skill division comprises businesses that present economic services through the utilization of techniques and organizations that deliver technical creations to banks unswervingly. Fintech